The Effect of Level of Education and Training on Employee Performance at PT. Japfa Comfeed Indonesia Tbk. Unit – Ps Tompobulu 1 Maros Regency - Mochtar Luthfi M; Nurlinda Nurlinda; Muliati Muliati; Mahyus Mahyus; Norhaedah K (Jurnal Office, 2023)
This research is to test and analyze: (1) The effect of educational level on employee performance. (2) The effect of training on employee performance. (3) The effect of the level of education and training simultaneously on the work performance of employees of PT. Japfa Comfeed Indonesia Tbk. Unit-PS Tompobulu 1 Maros Regency. The type of research used is quantitative research with data collection techniques using exact science, namely through observation, questionnaires and documentation with data analysis techniques using multiple linear regression analysis. The time used in this study was one month from January 2023 from the issuance of the permit. study. The results of the study show that: (1) The level of education has a significant effect on employee performance, with t count = 5, 972 > t table 1.671 and a significance of 0.000. (2) Training has a significant effect on employee performance, with t count = 7.568 > t table 1.671 and a significance of 0.000. (3) The level of education and training simultaneously has a significant effect on employee performance, with f count = 261.908 > f table 3.16, and a significance of 0.000.